Analisis Kinerja Keuangan Perusahaan Industri Sub-Sektor Farmasi yang Tercatat pada Indonesia Stock Exchange (IDX) - Sari, Delvi Novita; Rahmi, Elvi (Jurnal Ecogen, 2024)
This research aims to evaluate end clarify variations in financial overall effectiveness prior to , all through and after COVID-19, in pharmacological commercial agencies indexed at the Indonesia Stock Change (IDX). Research used is quantitative studies. This studies method is comparative information.  The population in this study was 288 populations. Providing secondary information with a sampling approach using purposive sampling with a sample size of 240 samples. This research technique is comparative statistics. Data testing was carried out only using the anova examination method which was calculated using the Statistical Bundle Social Sciences (SPSS) software program.  The Result of  this research show that there are not any good sized differences in liquidity ratios before, at some point of and after COVID-19. There are not any great differences in profitability ratios before, for the duration of and after COVID-19. The solvency ratio remains relatively consistent before, during, and after the impact of COVID-19, without any significant variations. There are good sized variations in interest ratios before, at some stage in and after COVID-19. So only the interest ratio is one of a kind earlier than, at some point of and after COVID-19. this is due to a lower overall asset turnover which isn't utilized optimally and does no longer make a contribution to earnings. aside from that, there are rules at some stage in COVID-19 which mean that companies cannot manage their property optimally and demand for purchasing strength has reduced.